Methodological Characteristics and Future Directions for Plyometric Jump Training Research: A Scoping Review (2018)
Recently, there has been a proliferation of published articles on the effect of plyometric jump training, including several review articles and meta-analyses. However, these types of research articles are generally of narrow scope. Furthermore, methodological limitations among studies (e.g., a lack of active/passive control groups) prevent the generalization of results, and these factors need to be addressed by researchers. On that basis, the aims of this scoping review were to (1) characterize the main elements of plyometric jump training studies (e.g., training protocols) and (2) provide future directions for research. From 648 potentially relevant articles, 242 were eligible for inclusion in this review. The main issues identified related to an insufficient number of studies conducted in females, youths, and individual sports (~ 24.0, ~ 37.0, and ~ 12.0% of overall studies, respectively); insufficient reporting of effect size values and training prescription (~ 34.0 and ~ 55.0% of overall studies, respectively); and studies missing an active/passive control group and randomization (~ 40.0 and ~ 20.0% of overall studies, respectively). Furthermore, plyometric jump training was often combined with other training methods and added to participants’ daily training routines (~ 47.0 and ~ 39.0% of overall studies, respectively), thus distorting conclusions on its independent effects. Additionally, most studies lasted no longer than 7 weeks. In future, researchers are advised to conduct plyometric training studies of high methodological quality (e.g., randomized controlled trials). More research is needed in females, youth, and individual sports. Finally, the identification of specific dose-response relationships following plyometric training is needed to specifically tailor intervention programs, particularly in the long term. © 2018, Springer International Publishing AG, part of Springer Nature.